Truncation of some akan personal names - Adomako, Kwasi (Penerbit UKM, 2015)
This paper examines some morphophonological processes in Akan personal names with focus on the former process. The morphological processes of truncation of some indigenous personal names identified among the Akan (Asante) ethnic group of Ghana are discussed. The paper critically looks at some of these postlexical morpheme boundary processes in some Akan personal names realized in the truncated form when two personal names interact. In naming a child in a typical Akan, specifically in Asante‟s custom, a family name is given to the child in addition to his/her „God-given‟ name or day-name. We observe truncation and some phonological processes such as vowel harmony, compensatory lengthening, etc. at the morpheme boundaries in casual speech context. These morphophonological processes would be analyzed within the Optimality Theory framework where it would be claimed that there is templatic constraint that demands that the base surname minimally surfaces as disyllable irrespective of the syllable size of the base surname. The relatively high ranking of this minimality constraint, we claim in this paper, forces the application of the compensatory lengthening rule to ensure satisfaction of that constraint in the truncated forms.